Penerapan Augmented Reality Berbasis Android untuk Pembelajaran Organ Lambung Manusia - Fony Ferliana Widianingrum; Sugondo Hadiyoso; Suci Aulia (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The stomach is one of the digestive systems functioning as a medium to process and store food, as well as to get rid of harmful substances and absorb good substances for the body. Although elementary schools usually use the torso as a teaching aid to introduce the stomach organ, it is, in fact, very inflexible for elementary students as they have limited learning hours at school. Therefore, it is necessary to develop a stomach organ learning system that can be studied anytime and anywhere. In this study, an Android-based stomach organ learning application was designed by applying Augmented Reality (AR). To run this application, the user needs to install it first. After opening the application and selecting the desired menu, users can point the smartphone at the appropriate marker until the AR display appears. Based on the test results, the application cannot bring AR objects from the stomach organ in a dark place since the marker is not detected. The best distance for marker detection is 20 cm to 35 cm, with an average delay of 0.3 s in indoor conditions and 0.45 s in outdoor conditions.